Perbaikan Berkelanjutan Pada Sistem Penjadwalan Perkuliahan Dengan Penjadwalan Berbasis Aplikasi dan Website - Wresni Anggraini; Febri Novia Warman (Engineering, MAthematics and Computer Science (EMACS) Journal, 2019)
Lecture scheduling systems that made manually need longer time and should be made time after time (trial and error) because there are many constrains should be considered like: number of classes, number of lecturers, number of courses and number of students. Delay in publishing class schedule could cause disruption in the lecture process. As an eﬀort to continuous improvement, designing lecture schedule system based on application or website which easy to use by user was very needed. This research aims to design lecture scheduling information systems based on website and android in Industrial Engineering Department, Islamic State University Sultan Syarif Kasim Riau. This research also measures system success rate by using User Acceptance Testing (UAT). The fnding reveals based on UAT analysis to the information system of lecture scheduling designed, as an average, the success rate was 85.1% from 100% success expected.